Learning English With Assembl Edu- based Augmented Reality: Does The Learning Media Matter? - Rosyidah, Linda Imamatul; Khatijah, Asna; dwi fita heriyawati (Universitas Cokroaminoto Palopo, 2023)
This research purpose is to see the level of student’s interest in the use Assemblr Edu-based Augmented Reality. This research applied a Quantitative approach using a survey design. 15 students become participants in this research. In collecting the data, the researcher used a questionnaire. The result showed that almost all of the variables of items get a positive perception as a learning media, as shown by the highest mean of 3.47. It means that the media can assist students in learning, especially in describing an object's appearance in 3D views, where the students are more interested in describing an object. Students’ answers show that they agree that the Assemblrs-Edu application is fun and the Assemblr Edu application motivates students and makes students enthusiastic to learn English. The abstract of the research paper should contain the purposes, methodology, and findings of the study.